"Localness" in donburi rice bowls in a remote rural areas: The case of Noto Peninsula, Japan - Kunimitsu Yoshida (Research in Globalization, 2023)
This paper takes the example of "notobowl (Notodon)", which was created as a new "local dish" in the Oku-Noto region, a peripheral area at the tip of the Noto Peninsula, Japan, to showcase how local chefs selected local ingredients to serve on bowls of rice to promote the local characteristics of the Noto (or Oku-Noto) region. This research focuses on small-scale family businesses, in the context of globalization and the global market economy. Each restaurant used products that it had already been selling locally by recommodifying them with a Notodon theme, so that they could be sold in a larger market area. I conducted semi-structured interviews with restaurant managers and other people who were part of the production process. The interviews focused on how each restaurant came up with its original dish, which considered the restaurant's location, its existing operation, and the influence of outside actors. The interview questions also inquired about the effects of commodifying localness on small family businesses in peripheral areas. The interviews indicated that local small-scale businesses led the promotion of Notodon. The restaurants followed their own procedures when they served their local dishes, they encouraged tourists to consume their Notodon.
Keywords: 330; Commodification; Japan; Local food; Noto Peninsula; Notodon; Regional promotion